2012
DOI: 10.7189/jogh.02.020405
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the prevalence of epilepsy in Sub–Saharan Africa: A systematic analysis

Abstract: BackgroundEpilepsy is a leading serious neurological condition worldwide and has particularly significant physical, economic and social consequences in Sub–Saharan Africa. This paper aims to contribute to the understanding of epilepsy prevalence in this region and how this varies by age and sex so as to inform understanding of the disease characteristics as well as the development of infrastructure, services and policies.MethodsA parallel systematic analysis of Medline, Embase and Global Health returned 32 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 49 publications
(52 reference statements)
3
60
2
Order By: Relevance
“…1 The prevalence of active convulsive epilepsy in subSaharan Africa (SSA) is high and ranges from 2.2 to 58 per 1000 affecting an estimated 4.4 million people. 2 Preux and DruetCabanac 3 estimated that the median prevalence of epilepsy in SSA to be 15/1000 ranging between 0/1000 and 33.5/1000. The prevalence of epilepsy in SE Nigeria is 4.3 per 1000.…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of active convulsive epilepsy in subSaharan Africa (SSA) is high and ranges from 2.2 to 58 per 1000 affecting an estimated 4.4 million people. 2 Preux and DruetCabanac 3 estimated that the median prevalence of epilepsy in SSA to be 15/1000 ranging between 0/1000 and 33.5/1000. The prevalence of epilepsy in SE Nigeria is 4.3 per 1000.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic analysis study on the prevalence of epilepsy in sub-Saharan Africa showed that active epilepsy was estimated to affect 4.4 million people, while lifetime epilepsy was estimated to affect 5.4 million 5. Another meta-analysis showed that the median incidence of epilepsy was 50.4/100,000/year (33.6–75.6), while it was 45.0 (30.3–66.7) for high-income countries and 81.7 (28.0–239.5) for low- and middle-income countries 6.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the lifetime prevalence of epilepsy in the developed world is 5.8 per 1000 [6]. In sub-Saharan Africa, an estimated 4.4 million people have active epilepsy, defined as one or more seizures over the past five years [7]. …”
Section: Introductionmentioning
confidence: 99%